Ontogeny of Adaptive Antibody Response to a Model Antigen in Captive Altricial Zebra Finches - Killpack, Tess L. (Public Library of Science, 2012)
Based on studies from the poultry literature, all birds are hypothesized to require at least 4 weeks to develop circulating mature B-cell lineages that express functionally different immunoglobulin specificities. However, many altricial passerines fledge at adult size less than four weeks after the start of embryonic development, and therefore may experience a period of susceptibility during the nestling and post-fledging periods. We present the first study, to our knowledge, to detail the age-related changes in adaptive antibody response in an altricial passerine. Using repeated vaccinations with non-infectious keyhole limpet hemocyanin (KLH) antigen, we studied the ontogeny of specific adaptive immune response in altricial zebra finches Taeniopygia guttata. Nestling zebra finches were first injected at 7 days (7d), 14 days (14d), or 21 days post-hatch (21d) with KLH-adjuvant emulsions, and boosted 7 days later. Adults were vaccinated in the same manner. Induced KLH-specific IgY antibodies were measured using ELISA. Comparisons within age groups revealed no significant increase in KLH-specific antibody levels between vaccination and boost in 7d birds, yet significant increases between vaccination and boost were observed in 14d, 21d, and adult groups. There was no significant difference among age groups in KLH antibody response to priming vaccination, yet KLH antibody response post-boost significantly increased with age among groups. Post-boost antibody response in all nestling age groups was significantly lower than in adults, indicating that mature adult secondary antibody response level was not achieved in zebra finches prior to fledging (21 days post-hatch in zebra finches). Findings from this study contribute fundamental knowledge to the fields of developmental immunology and ecological immunology and strengthen the utility of zebra finches as a model organism for future studies of immune ontogeny.